Penyuluhan Fisioterapi Komunitas Terkait Pencegahan Kesemutan Di Posyandu Lansia Rw 2 Desa Klampok, Singosari - Putu Febby Sisilia Meliniawati; Nungki Marlian Yuliadarwati; Ratna Vidya Amelia (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
Elderly or senior citizen is someone who is over 60 years old. Elderly or old age is the final phase of the human life cycle. The elderly will experience degenerative diseases, one of which is neurosensory disease, namely paresthesia. Thus, there is a need to increase knowledge about paresthesia. The method provided in community physiotherapy activities is to provide education regarding the meaning, causes, risk factors, prevention, physiotherapist treatment and prevention. From the activities carried out at Posyandu RW 2, Klampok Village, Singosari District, Malang, East Java on Tuesday, October 24 2023, it can be concluded that it went smoothly and was well realized. The benefit of this counseling activity is to provide insight and knowledge regarding the prevention and treatment of tingling or paresthesia so that the knowledge of the elderly regarding paresthesia increases.